2013
DOI: 10.15204/jkobgy.2013.26.2.178
|View full text |Cite
|
Sign up to set email alerts
|

A Report on the Effect of Jowisengchung-tang in 2 Cases of Precocious Puberty

Abstract: Objectives: These cases are that of three girls who are diagnosed as precocious puberty. It seems that the incidence of precocious puberty is rapidly increasing these days. In addition to the psychosocial disturbances associated with precocious puberty, the premature pubertal growth spurt and the accelerated bone maturation result in reduced adult height. The aim of this study was to report the effect of Jowisengchung-tang in 3 cases of precocious puberty.Methods: Retrospective and comparative analysis of 3 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…After 2nd round treatment, it was seen that breast buds had been disappeared. Other previous report, "Kim et al" gained almost identical clinical effect 10) . However, it is hard to acknowledge medicinal effect.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…After 2nd round treatment, it was seen that breast buds had been disappeared. Other previous report, "Kim et al" gained almost identical clinical effect 10) . However, it is hard to acknowledge medicinal effect.…”
Section: Discussionmentioning
confidence: 67%
“…However, some patients were hesitant about GnRH treatment for adverse effects 7,8) . Several researches reported that herbal medicine prescribed for those children suffering from PP has a certain effect on their symptoms 9,10) . However, reports are problematic in that there were no peak-LHL evaluation and made a simple comparison with breast buds or estradiol values of before and after taking the medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on PP have mainly focused on the effectiveness of GnRHa and herbal medicines [ 13 , 14 , 18 , 19 ], psychological characteristics of patients (not their caregivers) [ 20 ], and causes of PP [ 1 ]. Most studies on the caregivers of patients with PP have focused on the stress level and quality of life among caregivers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…ICPP, which accounts for the highest percentage of PP and is free from other identifiable diseases, can benefit from TKM [11]. Several studies too have reported the effectiveness of TKM on ICPP [13][14][15]. e management of a child's environment or habits is largely influenced by caregivers, and treatment is also dependent on caregivers' choices [16].…”
Section: Introductionmentioning
confidence: 99%